ОСОБЕННОСТИ ИЗМЕРЕНИЯ ПЛОТНОСТИ ПОТОКА НА ДЕКАМЕТРОВЫХ ВОЛНАХ - Шепелев, В. А.; Рашковский, С. Л.; Ломакин, Н. П. (Одеські астрономічні публікації, 2011)
Dependence of a flux density evaluated with long array on scintillation index is determined at the decameter wavelengths. Experimental dependence is in a good accordance with a model calculation.